Non-dairy Milk from Sprouted and Un-sprouted Soybeans Boiled in Plant Ash and Sodium Bicarbonate Solutions: A Comparative Nutrient, Physicochemical and Acceptability Responses - Okwunodulu, Innocent; Nwagwu, Francis; Okwunodulu, Felicia; Uluocha, Daniel (PUI BiGME Universitas Jambi, 2025)
Conventional uses of sodium bicarbonate in food processing result in gastrointestinal (GI) upset with such symptoms as nausea, stomach diarrhea, and vomiting to the venerable. Plant ash from empty palm bunch which is readily available, economical, underutilized, nutrient dense, and a tenderizer without side effects becomes the best alternative. Sorted and 12 h steeped soybean was sprouted (72 h) on a jute bag spread on the floor and covered with black polythene. The sprouts and un-sprouted soybeans were boiled (20 min) in water extract of plant ash of concentrations 30, 50, 70% and 0.5% sodium bicarbonate separately and hand de-hulled after cooling. The hulls were removed by water floatation and their cotyledons were milled with 93oC water (1 kg in 2.7 L) in variable kitchen blender, sieved with double layer calico cloth and the soymilk boiled for 20 min in open pan with continuous steering. The soymilk samples were separately analyzed. The results showed that with decrease in plant ash concentration, moisture, fiber, ash, fat, energy, pH, viscosity and appearance of soymilk from sprouted soybean increased more than their un-sprouted counterparts. Also, soymilk from sprouted soybean boiled in 0.5% sodium bicarbonate increased more than the un-sprouted counterparts in protein, vitamin C, calcium, phosphorous, iron, total soluble solids, pH, vitamin A and B1. There was no significant (p>0.05) in the acceptability of the entire soymilk samples, but those from sprouted soybeans were slightly better with more nutrient improvement at low ash concentration levels.